A decision model for selecting a safety data sheet management system using fuzzy TOPSIS. (15th April 2020) - Ahmed, Abdulaziz; Naji, Ahmed; Tseng, Ming-Lang
Abstract : Purpose: Safety data sheets are documents developed by chemical manufacturers to identify and label hazardous materials. The occupational safety and health administration regulations state that employers must make safety data sheets available for employees. When firms use hundreds of chemicals, tracking their safety data sheets becomes difficult. Safety Data Sheet Management Systems are developed to track safety data sheets. This paper aims to propose a multi-attribute decision-making framework for selecting a Safety Data Sheet Management System. Design/methodology/approach: A total of 12 attributes are proposed based on a real-life project conducted at a firm in New York and the software selection models existed in the literature. Fuzzy technique for order of preference by similarity to ideal solution is used to assess the proposed attributes and alternatives. A case study and sensitivity analysis are conducted to show the robustness of the proposed model. Fuzzy analytical hierarchy process is used for validation. Findings: Safety Data Sheet Management System is important for firms to track and manage safety data sheets. The proposed framework is practical and easy to implement. Practical implications: The proposed decision model is useful for firms to select a proper Safety Data Sheet Management System. The system developers can use the model to update their systems. Originality/value: This paper develops a new multi-attribute decision-making model for selecting a Safety Data Sheet Management System. To the best of the authors' knowledge, no previous study has developed such a model.